‘MIND MAPPING GAME’ USING PICTURES TO IMPROVE STUDENTS VOCABULARY - Januari Fitri; Regina Regina; Yohannes Gatot Sutapa Yuliana (ICoTE Proceedings, 2019)
This article aimed to describe about the use of mind mapping game using pictures to improve students’ vocabulary. The use of mind mapping game using pictures is important for students’ junior high school of suburban areas. Mind mapping’ game can make students have fun in learning. Visual or using picture the students can see the real of words. Vocabulary is important for students in the suburban school, because they never learn about English before. Then, the teacher have guide them how to write, read, translate and remember the vocabulary. Teacher want introduce English.  In order that, students have progress in learning and students’ vocabulary. The research methodology uses Classroom Action Research (CAR).